Origin and Position of Cystic Artery in Bangladeshi Corpse - Khalil, Mohsin; Sultana, Zinat Rezina; Rahman, Habibur Rahman; Sultana, Seheli Zannat; Mannan, Sabina; Rahman, Md Mahbabur; Ahamed, M Shibbir; Chowdhury, Md Ashraful Islam (Journal of Bangladesh Society of Physiologist, 2009)
This cross sectional descriptive morphological study was done to see the site of origin of cystic artery supplying the gallbladder in Bangladeshi people to increase the knowledge regarding variation anatomy in our population. Sixty post mortem tissue blocks containing liver and gallbladder along with surrounding structures were collected from 40 male and 20 female cadavers of different age groups and fixed in 10% formal saline solution. This study was carried out in the Department of Anatomy in Mymensingh Medical College, Mymensingh , from July 2007 to June 2008. Gross and fine dissections were carried out to study the different origin of cystic artery and its topographic relationship with adjacent structures. In the present study, findings were compared with the findings of Western researchers. In the present study, the so-called typical origin of the cystic artery from right hepatic artery was 90% and in 10% cases it was found to arise from other sources. Out of 10%, 3% arise from left hepatic artery, 3% from junction between right and left hepatic artery, 2% from hepatic artery proper and 2% from gastro duodenal artery. Key Words: Cystic artery, Origin, Location. Â doi: 10.3329/jbsp.v3i0.1801 J Bangladesh Soc Physiol.2008 Dec;(3):66-70.